Isoviolanthin promotes Schwann cells activity in peripheral nerve regeneration via Fhl3-mediated epithelial-mesenchymal transition-like process: An in vitro study - Yajuan Su; Tiantian Liu; Minjun Zhao; Dandan Wu; Yuehua Wang; Xubo Wu (Heliyon)
Schwann cells, as crucial regenerative cells, possess the ability to facilitate axon growth following peripheral nerve injury. However, the regeneration efficiency dominated by Schwann cells is impaired by factors such as the severity of peripheral nervous injury, aging, and metabolic disease. Cause the limitations of clinical treatments, it is necessary to urgently search for new substances that could reinforce the functionality of Schwann cells and promote nerve regeneration. We represented the first evidence that isoviolanthin possesses the capability to enhance Schwann cell proliferation and migration. Then, transcriptome sequencing was employed to examine the Differential Expressed Genes (DEGs), resulting in the identification of 193 DEGs. Following this, the expression levels of the top 5 up-regulated genes were confirmed through RT-qPCR, with Fhl3 demonstrating the most significant up-regulation. Schwann cells were transduced with virus particles made in HEK-293T/17 cells by transfection with lentivirus packaging plasmids containing Fhl3. A notable enhancement in Schwann cell proliferation and migration was observed following transduction. Furthermore, the Fhl3-up group exhibited a significant upregulation of Vimentin expression compared to the control group. These results suggested that isoviolanthin plays a positive role in enhancing Schwann cells' activity via increasing Fhl3 expression, and the mechanism may be related to the EMT(epithelial-mesenchymal transition)-like process.